2020
DOI: 10.1055/s-0040-1709711
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Major Adverse Limb Events in Patients with Peripheral Artery Disease: A Systematic Review and Meta-Analysis

Abstract: Background Statins are guidelines recommended in patients with peripheral artery disease (PAD) for the prevention of cardiovascular (CV) events. Comprehensive meta-data on the impact of statins on major adverse limb events (MALE) in PAD patients are lacking. We examined the association of statin use with MALE in patients with PAD. Methods We performed a systematic review (registered at PROSPERO: number CRD42019137111) and metanalysis of studies retrieved from PubMed (via MEDLINE) and Cochrane (CENTRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 76 publications
1
46
0
Order By: Relevance
“…A recent metanalysis has shown that statin therapy may prevent limb events in patients with PAD 31 . In our study, patients with PAD were more prone to receive statin therapy; however, in the light of this recent publication statin therapy should be more widely implemented.…”
Section: Discussionmentioning
confidence: 53%
“…A recent metanalysis has shown that statin therapy may prevent limb events in patients with PAD 31 . In our study, patients with PAD were more prone to receive statin therapy; however, in the light of this recent publication statin therapy should be more widely implemented.…”
Section: Discussionmentioning
confidence: 53%
“…46 Its cost-effectiveness and budget impact were highlighted by Cortesi et al 47 Often underestimated, the risk of major adverse limb events is unfortunately very high in patients with peripheral artery disease. Pastori et al 48 reported a well relayed comprehensive meta-analysis to alert physicians on the positive impact of statins for this group of patients.…”
Section: Aside From Anticoagulationmentioning
confidence: 99%
“…Venous thromboembolism (VTE) has an estimated annual incidence rate of 1–2 per 1000 person-years among people of European ancestry [ 1 ]. The 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitors, the so-called statins, are a class of lipid-lowering drugs widely used to prevent arterial atherosclerotic disease [ 2 ].…”
Section: Introductionmentioning
confidence: 99%